A Review of GNSS/GPS in Hydrogeodesy: Hydrologic Loading Applications and Their Implications for Water Resource Research. Issue 7 (8th July 2022) - White, Alissa M.; Gardner, W. Payton; Borsa, Adrian A.; Argus, Donald F.; Martens, Hilary R.
Abstract: Hydrogeodesy, a relatively new field within the earth sciences, is the analysis of the distribution and movement of terrestrial water at Earth's surface using measurements of Earth's shape, orientation, and gravitational field. In this paper, we review the current state of hydrogeodesy with a specific focus on Global Navigation Satellite System (GNSS)/Global Positioning System measurements of hydrologic loading. As water cycles through the hydrosphere, GNSS stations anchored to Earth's crust measure the associated movement of the land surface under the weight of changing hydrologic loads. Recent advances in GNSS‐based hydrogeodesy have led to exciting applications of hydrologic loading and subsequent terrestrial water storage (TWS) estimates. We describe how GNSS position time series respond to climatic drivers, can be used to estimate TWS across temporal scales, and can improve drought characterization. We aim to facilitate hydrologists' use of GNSS‐observed surface deformation as an emerging tool for investigating and quantifying water resources, propose methods to further strengthen collaborative research and exchange between geodesists and hydrologists, and offer ideas about pressing questions in hydrology that GNSS may help to answer. Plain Language Summary: Hydrogeodesy is a relatively new discipline within the earth sciences that analyzes the storage and movement of water at or near Earth's surface using measurements of Earth's shape, orientation, and gravitational field. In this paper, we review the current state of hydrogeodesy, focusing on the use of Global Positioning System and Global Navigation Satellite System (GNSS) to measure water masses as they change over time and in location. GNSS stations are anchored directly to Earth's crust and measure the movement of the land surface under the weight of changing (i.e., addition, loss, or movement) water masses. Herein, we describe how GNSS position time series respond to changing inputs of rain and snow and variable water loss, how they can be used to estimate the distribution of terrestrial water storage over time, and how they can improve drought characterization. We assert that GNSS‐based hydrogeodesy is an emerging tool that hydrologists can use to investigate and quantify water resources and we seek to explain and facilitate its use, propose methods to further strengthen collaborative research and exchange between geodesists and hydrologists, and offer ideas about pressing questions in hydrology that GNSS may help to answer. Key Points: Hydrogeodesy analyzes the distribution and movement of terrestrial water using measurements of Earth's shape, orientation, and gravity We review the current state of hydrogeodesy, focusing on Global Navigation Satellite System (GNSS) measurements of hydrologic loading and terrestrial water storage We aim to facilitate the use of GNSS‐observed surface deformation as an emerging tool for investigating and quantifying water resources